Bukti-Bukti Leksikal Pembeda Bahasa Wanokaka dan Anakalang di Sumba NTT - I Gede Budasi (Balai Bahasa Nusa Tenggara Barat, 2010)
Wanokaka (Wn) and Anakalang (An) languages are two of the seven languages spoken in Sumba, East Nusa Tenggara. Their speakers live in Central Sumba Regency in East Nusa Tenggara Province. Some linguists have considered the two are dialects of Sumba language. In Budasi’s study (2007 2009), however, both of them were quantitatively proved as two diffrent languages spoken in the regency. Based on the lexicostatistics analysis and Swadesh’s classification of language, the relatedness of the two languages was 75,5 % which means that they belong to language family (They are not in dialects relationship). Both languages were hyphotesized originally from Proto Wn-An in Sumba Language Group. Based on this hyphothesis, this paper aims at describing qualitatively the the lexical evidences which differ the two languages. In this study, the the compartive method was applied. The population of the study were the speakers of the two languages. Three informant samples were selected based on a set of criteria. The instruments of the data gathering were three word lists: Swadesh, Nothofer, and Holle; and a tape recorder. Two types of data: secondary and primary, were collected. The obtained data were analysed descriptively and qualitattively. This study concludes that 24.5 % of the total lexicons identified from the three word lists are in different forms that differed the two laguages lexically. Thereare two types of findings. The first findings are a number of lexicons which show the forms of lexical innovation, that is, the forms of cognat sets which show minimum differences in the their phonological patterns; and. The second, is that, the existance of lexical retentions generated from the Proto Wn-An. The whole identified evidences confirmed the quantitatif data findings mentioned in Budasi’s study (2007 and 2009), that is, the Wn-An are two different languages generated directly from the Proto Wn-An within Sumba language Group.